Brill's Companion to the Reception of Sophocles - Lauriola, Rosanna (Brill's Companions to Classical Reception Ser, 2017)
Intro -- Contents -- Preface and Acknowledgements -- List of Contributors -- Introduction: Ancient (and Byzantine) Perspectives on Sophocles' Life and Poetry -- Part 1 The Tragedies of War -- Chapter 1 Ajax -- Chapter 2 Philoctetes -- Part 2 The Tragedy of Destiny -- Chapter 3 Oedipus the King -- Chapter 4 Oedipus at Colonus -- Part 3 The Heroines' Tragedies: Sisters, Daughters, and Wives -- Chapter 5 Antigone -- Chapter 6 Electra -- Chapter 7 The Women of Trachis -- Appendix Not Only Tragedy: The Fragmentary Satyr Play -- The Trackers -- Index Locorum -- Index of Modern Adaptations -- Index of Subjects.